Creation of unequal error protection codes for two groups of symbols - Kuriata, Eugeniusz (Zielona Góra: Uniwersytet Zielonogórski)
This article presents problems of unequal information importance. The paper discusses constructive methods of code generation, and a constructive method of generating asymptotic UEP codes is built. An analog model of Hamming`s upper bound and Hilbert`s lower bound for asymptotic UEP codes is determined.
Keywords: unequal error protection codes (UEP codes); perfect codes; Hamming`s upper bound; Hilbert`s lower bound; generation matrix